PERCEPTIONS OF ENGLISH LANGUAGE TEACHERS ON CODE-SWITCHING APPROACH TOWARDS LANGUAGE DEVELOPMENT : Received: 16th August 2021; Revised: 19th January 2022, 26th February 2022; Accepted: 04th March 2022 - Makena, Bulelwa; Mpahla, Ntando (PUPIL: International Journal of Teaching, Education and Learning, 2022)
This paper explores how code-switching can be meaningfully used as an empowerment approach towards improving learners’ performance in the English language. In cultures with people using more than one language for communication, code-switching exists. Bilinguals as speakers of many languages, code-switch, using their languages resourcefully at conveying meaning in a variety of ways. Code-switching occurs every day during teaching and learning as most subjects in the curriculum are offered in the English language. Teaching and learning the English language in South Africa is characterized by serious challenges because the government is advocating for use of home languages for all subjects of lower grades in primary schools. However, teachers still encounter challenges when using English as a medium of instruction in preceding grades because learners fail to comprehend challenging concepts and terminologies presented to them in a language besides their home language. This qualitative study revealed that using code-switching can be a worthwhile approach for use in bilingual classrooms. A possible recommendation is that English language teachers should utilize code-switching as an approach to assist language development as learners in schools investigated emanate from diverse cultures, underpinned by different linguistic backgrounds and linguistic constituencies.